Enhancing Students Anti-Corruption Competence Through Corruption Prevention Campaigns In Social Media - Nurhana, Riza; Muntaha, Muntaha (Widya Yuridika, 2024)
Anti-corruption education courses were given to tertiary level students in Indonesia as an insertion or independent course to meet the challenge in reducing the number of corruptions from educated citizens. Although it does not guarantee that students will not commit acts of corruption in the future, through this anti-corruption education students are expected to be able to realize and understand behavior that leads to corruption and its consequences; so that students have choices and considerations to not commit acts of corruption. One of the learning methods used in anti-corruption courses is anti-corruption campaigns through social media. This method seeks to accommodate students' preferences for digital media, especially social media, and appreciates students' creativity in translating anti-corruption concepts through the perspective of young people. This study uses the Classroom Action Research (CAR) design by Kemmis and Mc. Taggart which was successfully delivered in 1 cycle consisting of planning, implementation/ acting, observing and reflecting stages. The research was carried out in the odd semester of the 2022/2023 academic year from September to November 2022 with the research subjects were the 5th semester students of the Academic Stage of Nursing Education Study Program consisting of 44 students. The results of the study indicated that learning methods that utilized social media in campaigning against corruption were able to increase students' understanding about corruption, corrupt behavior, anti-corruption values and improve students' abilities in making posters or videos. In addition, the methods were also able to improve the students’ motivation in learning during anti-corruption education class